What's the Deal? The Making, Shaping and Negotiating of First-Year Students' Psychological Contract With Their Personal Tutor in Higher Education - Yale, Annabel (Frontiers in Education, 2020)
The Psychological Contract is widely used to study employer-employee relationships, but few studies have applied it to a higher education context. This research examines the usefulness of psychological contract theory to explore the student-personal tutor relationship from the student perspective. In-depth interviews with first year undergraduates revealed new insights into the formation of the psychological contract and the dynamic nature of this relationship. When experiencing a conflict, discrepancy or breach to their perceived contract with their personal tutor, students undertake a complex sense-making attribution process and attempt to rebalance their psychological contract. The findings revealed the vital role the personal tutor has in the making, shaping and negotiating of the student’s psychological contract which goes beyond the bounds of that specific relationship to the contract students have with the institution. The research highlights the potential uses of psychological contract theory to uncover and negotiate the ‘deal’ students have with the university. The findings are useful for those working within the UK but offer insights that could be transferred to other international contexts in terms of understanding the psychological contracts of their students with the PT and the institution.